PMF Psychological Resilience in Pregnant Women During Pregnancy - Putu Monna Frisca Widiastini; Indrie Lutfiana; Cindy Meilinda Sari (Indonesian Journal of Global Health Research, 2024)
Psychological resilience during pregnancy is crucial for maintaining maternal mental health and influencing overall pregnancy outcomes. Despite its importance, the factors contributing to resilience and the effectiveness of interventions to enhance it are often underexplored. Objective: This study aims to investigate the impact of psychological resilience on pregnant women and assess the effectiveness of resilience-building interventions in improving maternal well-being and coping mechanisms. Method: A quasi-experimental design was employed with a treatment group and a control group, each consisting of Sixty (60) pregnant women selected through purposive sampling. The intervention involved resilience-enhancing workshops and support sessions facilitated online via the Zoom platform. The control group received standard prenatal care without additional interventions. Data were analyzed using the Mann-Whitney test, unpaired t-test, chi-square test, and Fisher’s exact test. Results: The three-month intervention significantly improved psychological resilience, as indicated by enhanced coping skills, reduced levels of anxiety and depression, and improved overall maternal well-being. Participants in the intervention group reported better stress management and increased satisfaction with prenatal care compared to the control group. Conclusions: Psychological resilience is a key factor in supporting pregnant women through the challenges of pregnancy. Effective resilience-building interventions can lead to significant improvements in maternal mental health and overall pregnancy outcomes.